FROM KNOWLEDGE TO ACTION: EMPOWERING INDONESIAN MIGRANT WORKERS THROUGH FINANCIAL LITERACY - Krissanya, Nofriska; Mahfirah, Titis Fatarina; Handaru, Agung Wahyu; Zakaria, Adam; Ahmad, Gatot Nazir; Anggraini, Ratna; Kurniaty, Kurniaty; Amirah, Aisyah (Yayasan Education and Social Center, 2024)
This article presents a community service initiative aimed at enhancing the financial literacy and entrepreneurial skills of Indonesian migrant workers in Malaysia, contributing to the Sustainable Development Goals (SDGs) of No Poverty (SDG 1) and Quality Education (SDG 4). Migrant workers often face significant barriers, including limited financial literacy and access to entrepreneurial opportunities, which hinder their socioeconomic advancement. The initiative, executed through a webinar titled